The Role of Dietary Supplementation in the Prevention of Macular Degeneration: An Analysis of the Efficacy of Vitamins and Antioxidants in Inhibiting the Progression of Macular Degeneration - Sebastian Mrugała; Waldemar Mrugała; Jakub Kawka; Alicja Baranowska; Katarzyna Baranowska; Filip Czyżewski; Kinga Filipek; Michał Muciek; Bartosz Skierkowski; Natalia Zalewska (Journal of Education, Health and Sport)
Age-related macular degeneration (AMD), one of the leading causes of vision loss among the elderly, poses a significant global health issue. This is a retinal condition that causes the loss of central vision. The demographic shift towards an aging population contributes to the increasing number of individuals affected by this condition, presenting a challenge to the medical and scientific community in developing effective prevention and treatment methods. In recent years, considerable attention has been given to the role of a proper diet and the supplementation of vitamins and antioxidants in inhibiting the progression of AMD.